Strategi Sosial Media Marketing di Platform Instagram: Studi Kasus Toko Aimas Bouquet - NUR AFNI KHAIRUNISA; Fhawujiah Ika Nur Aisyah Putri; Virgie Dimitria Teresa Sekewael; Melati Silva Lestari Manuputty; Abigael Sriyani Ranteangin; Madina Ayu Athifa A. Kadir (REMB : Research Economics Management and Business, 2026)
Social media marketing is now widely used by various groups, including MSMEs, such as Aimas Bouquet Shop. This study aims to explore the challenges and opportunities faced by Aimas Bouquet Shop, which implements social media marketing strategies on the Instagram platform, specifically the use of Instagram Stories and Instagram Reels to increase audience engagement. This study used qualitative methods through observation and in-depth interviews with the owner of Aimas Bouquet Shop, who uses Instagram as a primary marketing platform. The results show that Aimas Bouquet Shop consistently maintains its promotional strategies, increases followers, maintains positive interactions with consumers, reaches non-followers, and expands its market segment.